Tuning T‐Cell Receptor Affinity to Optimize Clinical Risk‐Benefit When Targeting Alpha‐Fetoprotein–Positive Liver Cancer. Issue 5 (14th February 2019) - Docta, Roslin Y.; Ferronha, Tiago; Sanderson, Joseph P.; Weissensteiner, Thomas; Pope, George R.; Bennett, Alan D.; Pumphrey, Nicholas J.; Ferjentsik, Zoltan; Quinn, Laura L.; Wiedermann, Guy E.; Anderson, Victoria E.; Saini, Manoj; et al.
Abstract : Patients with hepatocellular carcinoma (HCC) have a poor prognosis and limited therapeutic options. Alpha‐fetoprotein (AFP) is often expressed at high levels in HCC and is an established clinical biomarker of the disease. Expression of AFP in nonmalignant liver can occur, particularly in a subset of progenitor cells and during chronic inflammation, at levels typically lower than in HCC. This cancer‐specific overexpression indicates that AFP may be a promising target for immunotherapy. We verified expression of AFP in normal and diseased tissue and generated an affinity‐optimized T‐cell receptor (TCR) with specificity to AFP/HLA‐A*02 + tumors. Expression of AFP was investigated using database searches, by qPCR, and by immunohistochemistry (IHC) analysis of a panel of human tissue samples, including normal, diseased, and malignant liver. Using in vitro mutagenesis and screening, we generated a TCR that recognizes the HLA‐A*02‐restricted AFP158‐166 peptide, FMNKFIYEI, with an optimum balance of potency and specificity. These properties were confirmed by an extension of the alanine scan (X‐scan) and testing TCR‐transduced T cells against normal and tumor cells covering a variety of tissues, cell types, and human leukocyte antigen (HLA) alleles. Conclusion: We have used a combination of physicochemical, in silico, and cell biology methods for optimizing a TCR for improved affinity and function, with properties that are expected to allow TCR‐transduced T cells to differentiate between antigen levels on nonmalignant and cancer cells. T cells transduced with this TCR constitute the basis for a trial of HCC adoptive T‐cell immunotherapy.